Морфологическая характеристика древнеанглийских дифтонгов преломления - Забулене, Лайма (Kalbotyra, 1987)
Short breaking diphthongs are more widely represented in the morphological system of OE than the corresponding long ones.The short diphthongs /ĕa ĕo ĭo/ are particularly numerous in the system of noun though there are suffixes with the diphthong /ĕa/ which are productive in other parts of speech as well: the suffix of adjectives and adverbs -weard(es) and the suffix of numerals -feald. In the system of verb both short and long breaking diphthongs are well attested.